2017
DOI: 10.1097/paf.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress and Burnout Symptoms in Forensic Doctors and Staff in a Mortuary

Abstract: We aimed to investigate burnout and posttraumatic stress symptoms in mortuary staff members who work for the Council of Forensic Medicine where more than 4500 autopsies are annually performed.The data were collected from 142 mortuary staff members from the Council of Forensic Medicine, Turkey. The participants were divided into the following 4 groups: forensic medicine specialists (n = 40, 28.2%), forensic medicine residents (n = 54, 38.0%), autopsy technicians (n = 24, 16.9%), and other staff members (n = 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Comparable results, 31.9%, 27.4%, and 22.2%, respectively, were reported by Elliott and Daley (2013). Whereas Kömür et al (2017) reported that 14% were highly emotionally exhausted, 32.4% were highly depersonalized, and 76.1% had a low sense of personal accomplishment level among mortuary staff members. The current study took moderate burnout levels into consideration, which mostly accounts for differences in prevalence.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Comparable results, 31.9%, 27.4%, and 22.2%, respectively, were reported by Elliott and Daley (2013). Whereas Kömür et al (2017) reported that 14% were highly emotionally exhausted, 32.4% were highly depersonalized, and 76.1% had a low sense of personal accomplishment level among mortuary staff members. The current study took moderate burnout levels into consideration, which mostly accounts for differences in prevalence.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, forensic pathologists' job is mainly in the laboratory examining specimens from crime scenes. Similarly, Kömür et al (2017) found higher burnout in those performing autopsies than other mortuary staff, and Iorga et al (2016) reported higher emotional exhaustion among forensic physicians who faces critical situation.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations